2015
DOI: 10.1007/s00213-015-4150-4
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hippocampal plasticity in rats performing contrafreeloading for water under repeated administrations of pramipexole

Abstract: Rationale Compulsive symptoms develop in patients exposed to pramipexole (PPX), a dopaminergic agonist with high selectivity for the D3 receptor. Consistently, we demonstrated that PPX produces an exaggerated increase in contrafreeloading (CFL) for water, a repetitive and highly inflexible behavior that models core aspects of compulsive disorders. Objectives Given the role of the hippocampus in behavioral flexibility, motivational control, and visuospatial working memory, we investigated the role of hippocampu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…More recently, preclinical results have revealed that lesions in the hippocampal regions can cause a perseveration of certain behaviors (Kosaki and Watanabe, 2012;Chudasama et al 2012). Also in another model for compulsive behavior, characterized by the contrafreeloading of water that is induced by pramipexole (D3-agonist), a significant decrease in hippocampal long-term potentiation (LTP) was found (Schepisi et al 2015) Additionally, lower ratios of N-acetyl-l-aspartate/choline (NAA/CHO) were found in OCD patients when compared to healthy controls (Atmaca et al 2009) in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, preclinical results have revealed that lesions in the hippocampal regions can cause a perseveration of certain behaviors (Kosaki and Watanabe, 2012;Chudasama et al 2012). Also in another model for compulsive behavior, characterized by the contrafreeloading of water that is induced by pramipexole (D3-agonist), a significant decrease in hippocampal long-term potentiation (LTP) was found (Schepisi et al 2015) Additionally, lower ratios of N-acetyl-l-aspartate/choline (NAA/CHO) were found in OCD patients when compared to healthy controls (Atmaca et al 2009) in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%
“…However, some information can reasonably be deduced from current data. In rodents, PPX results in an increase in foraging activity on the harder food option (e.g., Johnson et al, 2011, 2012; Schepisi et al, 2013, 2016). Effort facilitation is compatible with the view that dopamine agonists enhance incentive motivational processes (Salamone & Correa, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Neurobiological investigations show that striatal dopamine is involved in suboptimal choices. In rats, contrafreeloading is enhanced after repeated injection of pramipexole (PPX)—a dopamine D2/3 receptor agonist (Schepisi, De Carolis, & Nencini, 2013; Schepisi et al, 2016). Also, rats given a choice between a variable ratio and a fixed ratio of responses to levers have a natural preference for variability, and this preference is increased after receiving an acute injection of PPX (Johnson et al, 2011, 2012).…”
mentioning
confidence: 99%
“…Contrafreeloading is the behavior of working for a resource that requires effort to obtain when also provided with a similar resource that is freely available 1 3 . Historically, this resource has been food, although contrafreeloading for water and other resources has also been studied [e.g., 4 ]. The presence of contrafreeloading behavior is particularly interesting given that it seems to oppose a basic tenet of animal learning and evolutionary theory, as well as optimal foraging theory 1 —that animals should maximize rewards and minimize costs 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%